Prenatal Yoga to Relief Back Pain among Pregnant Women - Budi Rahayu (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Back pain is a kind of discomfort that frequently develops during pregnancy, especially among pregnant women in late pregnancy or those with a history of back pain in previous pregnancy. Prenatal yoga can relief back pain discomfort since it promotes good posture and stretch the spine's central nervous system. This study aims to determine the effect of yoga exercise on back pain among pregnant women in the third trimester.This was a pre-experimental study with one group pretest posttest design. The current study involved 30 pregnant women in the third trimester, who were assigned into the treatment group (participated in prenatal yoga exercise) and the control group (did not participate in prenatal yoga exercise), consisting of 15 samples, respectively. The study instrument applied here was Faces Pain Scale-Revised a questionnaire (FPS-R). It was found that there was a significant effect of prenatal yoga exercise to relief back pain among pregnant women in the third trimester (p less than 0.05). It can be concluded that prenatal yoga was beneficial for relieving back pain among pregnant women in the third trimester. Thus, prenatal yoga technique is considered an appropriate method for supproting the succes of pregnancy.